Fasting increases investment in soma upon refeeding at the cost of gamete quality in zebrafish. Issue 1996 (12th April 2023) - Ivimey-Cook, Edward R.; Murray, David S.; de Coriolis, Jean-Charles; Edden, Nathan; Immler, Simone; Maklakov, Alexei A.
Abstract : Fasting increases lifespan in invertebrates, improves biomarkers of health in vertebrates and is increasingly proposed as a promising route to improve human health. Nevertheless, little is known about how fasted animals use resources upon refeeding, and how such decisions affect putative trade-offs between somatic growth and repair, reproduction and gamete quality. Such fasting-induced trade-offs are based on strong theoretical foundations and have been recently discovered in invertebrates, but the data on vertebrates are lacking. Here, we report that fasted female zebrafish, Danio rerio, increase investment in soma upon refeeding, but it comes at a cost of egg quality. Specifically, an increase in fin regrowth was accompanied by a reduction in 24 h post-fertilization offspring survival. Refed males showed a reduction in sperm velocity and impaired 24 h post-fertilization offspring survival. These findings underscore the necessity of considering the impact on reproduction when assessing evolutionary and biomedical implications of lifespan-extending treatments in females and males and call for careful evaluation of the effects of intermittent fasting on fertilization.